Subpopulation of Macrophage-Like Plasmatocytes Attenuates Systemic Growth via JAK/STAT in the Drosophila Fat Body - Shin, Mingyu; Cha, Nuri; Koranteng, Ferdinand; Cho, Bumsik; Shim, Jiwon (Frontiers in Immunology, 2020)
Drosophila hemocytes, like those of mammals, are given rise from two distinctive phases during both the embryonic and larval hematopoiesis. Embryonically derived hemocytes, mostly composed of macrophage-like plasmatocytes, are largely identified by genetic markers. However, the cellular diversity and distinct functions of possible subpopulations within plasmatocytes have not been explored in Drosophila larvae. Here, we show that larval plasmatocytes exhibit differential expressions of Hemolectin (Hml) and Peroxidasin (Pxn) during development. Moreover, removal of plasmatocytes by overexpressing pro-apoptotic genes, hid and reaper in Hml-positive plasmatocytes, feeding high sucrose diet, or wasp infestation results in increased circulating hemocytes that are Hml-negative. Interestingly these Hml-negative plasmatocytes retain Pxn expression, and animals expressing Hml-negative and Pxn-positive subtype largely attenuate growth and abrogate metabolism. Furthermore, elevated levels of a cytokine, unpaired 3, are detected when Hml-positive hemocytes are ablated, which in turn activates JAK/STAT activity in several tissues including the fat body. Finally, we observed that insulin signaling is inhibited in this background, which can be recovered by concurrent loss of upd3. Overall, this study highlights heterogeneity in Drosophila plasmatocytes and a functional plasticity of each subtype, which reaffirms extension of their role beyond immunity into metabolic regulation for cooperatively maintaining internal homeostatic balance.